THE CONCEPT OF التوبة IN AL-QUR’AN AND ITS APPLICATION - Achmad Ramadhan (UIN Sumatera Utara, 2021)
This study aims to describe the concept of At-Taubah in Al-Quran and its’ application. Descriptive qualitative study is used as the all paragraphs explain related literature to the concept of At-Taubah.